Dimensions of Omnichannel Retail Quality on Customer Satisfaction and Loyalty - Clara, Catharina - (Journal of International Conference Proceedings, 2023)
The shift in consumer shopping from offline to online, and then to a hybrid of the two, combining the benefits of each to overcome the disadvantages of both. This study focuses on the dimensions of omnichannel retail quality. The emphasis is on analyzing consumer behavior in offline, online, and combined omnichannel retail channels. The rapid growth of this retail channel is due in part to the ease and security of payment, though there are still those who use the cash-on-delivery system. The methods employed include a review of the literature on omnichannel research articles, consumer surveys, and data documentation on business phenomena. SEM was used to examine the relationship between IOC, VOC, CS, and CL. The software used is Smart PLS 4. The goal of path modeling, particularly reflective models such as PLS, is to estimate the variance of endogenous constructs, as a result from their respective manifest variables. The findings of this study can be used to test OC intensity and OC shopping value in providing consumers with shopping experiences that result in customer satisfaction and loyalty. Relevant marketing implications and future research are advised.